The effect of prenatal vaginal progesterone on cervical length in nonselected twin pregnancies. (18th April 2019) - Agra, Isabela K. R.; Carvalho, Mário H. B.; Hernandez, Wagner R.; Francisco, Rossana P. V.; Zugaib, Marcelo; Brizot, Maria L.
Abstract: Purpose: The aim of this study was to investigate the influence of vaginal progesterone on cervical length (CL) in asymptomatic nonselected twin gestations. Methods: This was a secondary analysis of a randomized, double-blind, placebo-controlled trial of twin pregnancies exposed to vaginal progesterone or placebo. The CL was examined at six different time periods: 18–21 +6 weeks (T1), 21–23 +6 weeks (T2), 24–26 +6 weeks (T3), 27–29 +6 weeks (T4), 30–32 +6 weeks (T5) and 33–34 +6 weeks (T6). The rate of cervical shortening per week and the percent cervical shortening were compared between the groups, with analyses of the entire cohort and of those who delivered spontaneously according to gestational age at birth. Results: The final analysis included 184 women in the progesterone group and 188 women in the placebo group. The baseline characteristics were similar in both groups. No differences in cervical shortening in terms of absolute value or percent shortening were observed between the groups at each time period or throughout gestation. Furthermore, no difference was found in cervical shortening for those who delivered spontaneously. Conclusion: Cervical shortening in asymptomatic nonselected twin pregnancies occurred at a similar rate, regardless of vaginal progesterone treatment.